Saints, Sages, and Victims: Endorsement of and Resistance to Cultural Stereotypes in Memoirs by Parents of Children with Disabilities - Piepmeier, Alison (Disability Studies Quarterly, 2012)
Memoirs written by parents of children with disabilities are a significant recent genre. Most are problematic: through their use of grief, their emphasis on a medicalized model, and their framing of the child's disabilities, these memoirs represent the child not as a person but as a problem with which the parents have had to grapple. Many memoirs, however, simultaneously work to humanize and value the children and reframe our cultural view of "typical" personhood through the lens of disability. This complex, popular genre reveals the powerful hold that formulaic narratives have, but also offers glimpses of ways in which formulaic narratives can and should be resisted and overturned. The books I examine demonstrate that the family can be a site that both bolsters oppressive cultural models of disability and profoundly challenges them. Keywords memoir, children with disabilities, parents, grief, dehumanization, pleasure, resistance